2015
DOI: 10.1124/dmd.115.067504
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Hepatic Drug-Metabolizing Enzymes in Germ-Free Mice by Conventionalization and Probiotics

Abstract: Little is known regarding the effect of intestinal microbiota modifiers, such as probiotics and conventionalization with exogenous bacteria, on host hepatic drug metabolism. Therefore, the goal of this study was to determine the effect of these modifiers on the expression of various drug-metabolizing enzymes of the host liver. VSL3 is a probiotic that contains eight live strains of bacteria. Five groups of mice were used: 1) conventional mice (CV), 2) conventional mice treated with VSL3 in drinking water, 3) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 38 publications
7
88
0
Order By: Relevance
“…Antibiotic treatment has been shown to induce farnesoid X receptor, inhibit intestinal bile acid reabsorption, change glucose metabolism, affect bile acid metabolism, and increase the blood concentration of α‐tocopherol in animals . Gut microbiota has also been shown to affect drug‐metabolizing enzymes . Although the increase of EGCG absorption caused by antibiotic treatment may contribute to the presently observed higher bioavailability of EGCG, the decreased microbial degradation of EGCG is the most straightforward interpretation of our present results.…”
Section: Discussionsupporting
confidence: 61%
“…Antibiotic treatment has been shown to induce farnesoid X receptor, inhibit intestinal bile acid reabsorption, change glucose metabolism, affect bile acid metabolism, and increase the blood concentration of α‐tocopherol in animals . Gut microbiota has also been shown to affect drug‐metabolizing enzymes . Although the increase of EGCG absorption caused by antibiotic treatment may contribute to the presently observed higher bioavailability of EGCG, the decreased microbial degradation of EGCG is the most straightforward interpretation of our present results.…”
Section: Discussionsupporting
confidence: 61%
“…Experimental models investigating the effects of the gut microbiota on drug metabolism and transport include un-colonized or germ-free animals. Germ-free and normally colonized mice differentially express important drug metabolism and transporter genes [33–36]. For example, germ-free mice exhibit increased expression of Cyp1a2 (+51%) and Cyp4a14 (+202%) mRNA, but decreased expression of Cyp3a11 (−87%) and Cyp2b10 (−57%) mRNA.…”
Section: Intestinal Microbiota-host Liver Interactionsmentioning
confidence: 99%
“…The microbiome can impact APAP metabolism through enzyme induction, enzyme inhibition, and enterohepatic circulation . Studies have shown that the gut microbiome can regulate the expression of intestinal SULTs, UGTs, and CYPs, as well as their hepatic counterparts in mice and rats . Additionally, p ‐cresol, an endogenous microbial metabolite, undergoes sulfation and can diminish APAP sulfation by competitive inhibition .…”
Section: Discussionmentioning
confidence: 99%